Experience of clinicians with dual bronchodilator therapy in COPD (EXPAND) in Nepal - Chokhani, Ramesh; Shrestha, Sanjeet Krishna; Bhattarai, Sharad; Mukhopadhyay, Aniruddha; Gaur, Vaibhav; Gogtay, Jaideep (Nepalese Respiratory Journal, 2023)
Introduction: Combination of bronchodilators, particularly long-acting muscarinic antagonists (LAMAs) and long-acting β2 agonists (LABAs) have become the mainstay of pharmacological therapy for COPD. COPD is now a common non communicable disease in Nepal. Objective: The study evaluated the current perception and experience of the clinicians in Nepal on diagnosis and management of COPD with focus on use of dual bronchodilator therapy. Method: This cross-sectional, observational survey evaluated experiences of clinicians (n=96; pulmonologist-13, physician-57, general practitioner-26) in Nepal on diagnosis, management trends, and current perceptions on the use of dual bronchodilator therapy in COPD management. Result: 93% of clinicians were practising in an urban setting for an average of 10 years and an average of 35% of their patients are of COPD. 61% of clinicians use mMRC with (34%) or without (27%) CAT score. 92% of clinicians perceived that most of their patients had 1 (32%) or >1 (59%) exacerbation/year. 54% of clinicians performed spirometry on all their patients with suspected COPD. 49% of clinicians measured blood EOS in their patients with severe COPD before adding ICS. 93% of clinicians preferred dual therapy (separate inhalers or a combination) for their COPD patients, but 83% of clinicians preferred LABA + LAMA in a single inhaler over inhalers given separately. 57% of clinicians preferred LABA + LAMA and 82% preferred the Tiotropium + Formoterol combination. 81% of clinicians stepped up or stepped down their treatment. 56% of patients were taking LABA + LAMA + ICS and 55% of clinicians co-prescribed ICS + LABA with LABA + LAMA. 80% of clinicians checked the inhalation technique at every visit and an average of 54% of their COPD patients were adherent (>80%) to the prescribed inhalation therapy. 78% of clinicians felt that dryness of mouth was the most common side effect of LABA + LAMA. 94% of clinicians believed that managing COPD better could improve cardiovascular outcomes in their patients with coexistent COPD. Conclusion: In the EXPAND survey, Formoterol + Tiotropium was preferred by most clinicians in Nepal amongst the LABA + LAMA combination. There is a good scope for improvement in the utilization of tools like spirometry, mMRC, CAT, and blood EOS in the daily practice of clinicians in Nepal.